Giles S. Rich papers - Rich, Giles S.
Correspondence, memoranda, writings, speeches, notes, opinion files, teaching files, printed matter, clippings, and other papers documenting Rich's career in patent and intellectual property law as a judge on the U.S. Court of Customs and Patent Appeals and its successor the U.S. Court of Appeals for the Federal Circuit. Includes material pertaining to patents in the biotechnology, computer software, and pharmaceutical industries; design protection; and the "nonobviousness" standard for patents. Correspondents include Tom Arnold, George E. Frost, Frank Y. Gladney, Learned Hand, Alan Latman, Paul P. Rao, Homer J. Schneider, Arthur M. Smith, and Robert C. Watson.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Library of Congress Anglo-American Acquisitions Division.
Federal judge and patent attorney. Full name: Giles Sutherland Rich. Born 1904; died 1999.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Arnold, Tom -- Correspondence; Frost, George E., -- 1918- -- Correspondence; Gladney, Frank Y. -- 1877- -- Correspondence; Hand, Learned, -- 1872-1961 -- Correspondence; Latman, Alan -- Correspondence; Rao, Paul P., -- 1899- -- Correspondence; Schneider, Homer J. -- Correspondence; Smith, Arthur M. -- 1903- -- Correspondence; Watson, Robert C. -- Correspondence; United States. -- Court of Appeals (Federal Circuit); United States. -- Court of Customs and Patent Appeals; Biotechnology -- Patents; Biotechnology industries; Computer software -- Patents; Computer software industry; Design protection; Intellectual property; Patent laws and legislation; Patents -- Standards; Pharmaceutical industry; Pharmaceutical industry -- Patents; Jurists; Lawyers